Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine which of the given factors, if any, is a factor of the polynomial [tex]\( x^3 + 12x^2 + 9x - 22 \)[/tex], we will use the factor theorem. The factor theorem states that [tex]\( x - a \)[/tex] is a factor of a polynomial [tex]\( P(x) \)[/tex] if and only if [tex]\( P(a) = 0 \)[/tex]. This means we should evaluate the polynomial at the roots associated with the given candidates (i.e., the opposites of [tex]\( a \)[/tex] for each factor [tex]\( x \pm a \)[/tex]) and see if the result is zero.
Let's evaluate the polynomial at the specific values corresponding to each factor:
1. [tex]\( x + 2 \)[/tex]:
- Candidate root: [tex]\( -2 \)[/tex]
- Substitute [tex]\( x = -2 \)[/tex] into [tex]\( P(x) \)[/tex]:
[tex]\[ P(-2) = (-2)^3 + 12(-2)^2 + 9(-2) - 22 = -8 + 48 - 18 - 22 = -8 + 48 - 40 = 0 \][/tex]
Hence, [tex]\( x + 2 \)[/tex] is a factor.
2. [tex]\( x - 2 \)[/tex]:
- Candidate root: [tex]\( 2 \)[/tex]
- Substitute [tex]\( x = 2 \)[/tex] into [tex]\( P(x) \)[/tex]:
[tex]\[ P(2) = 2^3 + 12(2)^2 + 9(2) - 22 = 8 + 48 + 18 - 22 = 8 + 48 + 18 - 22 = 52 \][/tex]
Hence, [tex]\( x - 2 \)[/tex] is not a factor.
3. [tex]\( x - 3 \)[/tex]:
- Candidate root: [tex]\( 3 \)[/tex]
- Substitute [tex]\( x = 3 \)[/tex] into [tex]\( P(x) \)[/tex]:
[tex]\[ P(3) = 3^3 + 12(3)^2 + 9(3) - 22 = 27 + 108 + 27 - 22 = 162 - 22 = 140 \][/tex]
Hence, [tex]\( x - 3 \)[/tex] is not a factor.
4. [tex]\( x + 1 \)[/tex]:
- Candidate root: [tex]\( -1 \)[/tex]
- Substitute [tex]\( x = -1 \)[/tex] into [tex]\( P(x) \)[/tex]
[tex]\[ P(-1) = (-1)^3 + 12(-1)^2 + 9(-1) - 22 = -1 + 12 - 9 - 22 = 2 - 22 = -20 \][/tex]
Hence, [tex]\( x + 1 \)[/tex] is not a factor.
So, the correct answer is:
A. [tex]\( x+2 \)[/tex]
Let's evaluate the polynomial at the specific values corresponding to each factor:
1. [tex]\( x + 2 \)[/tex]:
- Candidate root: [tex]\( -2 \)[/tex]
- Substitute [tex]\( x = -2 \)[/tex] into [tex]\( P(x) \)[/tex]:
[tex]\[ P(-2) = (-2)^3 + 12(-2)^2 + 9(-2) - 22 = -8 + 48 - 18 - 22 = -8 + 48 - 40 = 0 \][/tex]
Hence, [tex]\( x + 2 \)[/tex] is a factor.
2. [tex]\( x - 2 \)[/tex]:
- Candidate root: [tex]\( 2 \)[/tex]
- Substitute [tex]\( x = 2 \)[/tex] into [tex]\( P(x) \)[/tex]:
[tex]\[ P(2) = 2^3 + 12(2)^2 + 9(2) - 22 = 8 + 48 + 18 - 22 = 8 + 48 + 18 - 22 = 52 \][/tex]
Hence, [tex]\( x - 2 \)[/tex] is not a factor.
3. [tex]\( x - 3 \)[/tex]:
- Candidate root: [tex]\( 3 \)[/tex]
- Substitute [tex]\( x = 3 \)[/tex] into [tex]\( P(x) \)[/tex]:
[tex]\[ P(3) = 3^3 + 12(3)^2 + 9(3) - 22 = 27 + 108 + 27 - 22 = 162 - 22 = 140 \][/tex]
Hence, [tex]\( x - 3 \)[/tex] is not a factor.
4. [tex]\( x + 1 \)[/tex]:
- Candidate root: [tex]\( -1 \)[/tex]
- Substitute [tex]\( x = -1 \)[/tex] into [tex]\( P(x) \)[/tex]
[tex]\[ P(-1) = (-1)^3 + 12(-1)^2 + 9(-1) - 22 = -1 + 12 - 9 - 22 = 2 - 22 = -20 \][/tex]
Hence, [tex]\( x + 1 \)[/tex] is not a factor.
So, the correct answer is:
A. [tex]\( x+2 \)[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.